Inheritance Distribution in The Javanese Tondano Community - Bempa, Sofyan Winandi Putra; Puluhulawa, Fenty U. (Damhil Law Journal, 2021)
The purpose of this study was to analyze the inheritance distribution system of the Tondano Javanese people in the village of Tondano Reksonegoro and the settlement of inheritance disputes that occurred through the Alternative Dispute Resolution (ADR) for the Tondano Javanese community in Reksonegoro village, Tibawa district, Gorontalo regency. The nature of this research is descriptive qualitative with a socio-legal approach method—data obtained through direct interviews with subjects or informants. The data analysis technique consists of 4 steps: data collection, data reduction, data entry, and conclusion drawing or verification. The division of inheritance with a will is practiced by theTondano Javanese people in Reksonegoro Village, Tibawa District because there is a high possibility of disputes between the heirs. The division of inheritance with a will is also based on the suitability of the following three things, namely personal experience, seeing the surroundings/surroundings, and messages from parents. Results analysis of property dispute resolution through Alternative Dispute Resolution (ADR) in the Tondano community in Reksonegoro village, namely consultation, negotiation, and mediation. The three forms are widely used sequentially according to stages. The reasons for resolving property disputes through the Alternative Dispute Resolution (ADR) route are (1) upholding the principles of Ampit Watu Esa Pelayas, (2) Cultivating the cultural value of deliberation for consensus, (3) Upholding the value of gotong royong, (4) Reluctance towards settlement through court institutions, (5) Maintaining the pam or the good name and honor of the family, and (6) Preventing disputes from getting bigger and too long.